Anterior thoracic myelomeningocele presenting with neck pain: an unusual spinal dysraphism - Tanwar, Rekha; Mehra, Shibani; Gupta, Pooja; Singh, Shahsi Kumar (International Journal of Contemporary Pediatrics, 2025)
Cervicothoracic myelomeningocele is a rare entity with few cases reported in previous literature of anterior thoracic myelomeningocele. Spinal dysraphism (SD) is a congenital malformation of the spine involving the spinal cord which is characterized by incomplete midline closure of mesenchymal osseous and nervous tissue in the developing fetus. Early diagnosis of myelomeningoceles offers several benefits, including parental counselling, treatment planning, and reducing potential associated complications. MRI is the best modality to study soft tissue morphology of the cord as well as vertebral and discal pathologies. We report a case of 4-year-old female child presented with multiple episodes of neck pain of 1 year duration. The antenatal history was unremarkable except for lack of folic acid intake as a supplement during the pregnancy. There was mild kyphoscoliotic deformity in upper thoracic spine. Radiological imaging was done for further evaluation. MRI revealed herniation of a CSF containing thecal sac ventral to the spine protruding from D1 to D3 vertebral level through a midline defect with neural placode was seen within and tethering of the neural placode. On MRI, the radiological diagnosis of true anterior myelomeningocele was made. Congenital malformations of the spinal cord include a range of abnormalities with varying but distinctive imaging features thereby making MRI the best modality for evaluation and diagnosis. Radiologists and neurologists must both be aware of the wide spectrum of SD and the unusual presentations like neck pain or paraparesis, for early diagnosis and effective management. MRI of brain and spinal cord is the key in detection of anterior myelomenigocele which is an occult form of SD.